Nível nutricional na gestação de vacas de corte: eficiência reprodutiva e produtiva da prole - Adams, Sander Martinho (2023)
Nutritional restriction during fetal development has negative effects on its growth and development, which can compromise its performance. However, scientific studies that measured the extent of this compromise are scarce, inconsistent, and non-existent in the case of long-term evaluations. Therefore, the objective of this study was to evaluate the long-term impacts of nutritional levels during fetal development of beef cows on their productive and reproductive performance, as well as the impacts on the animals they generate. The treatments were formed according to the nutritional level during the final third of fetal development of cows: Low (cows allocated to native pasture and subjected to mild nutritional restriction), Medium (cows allocated to native pasture and supplemented to meet 100% of maintenance requirements), and High (cows allocated to native pasture and supplemented to meet 150% of maintenance requirements). Forty cows and the 64 calves they produced after being subjected to three reproductive periods were used. The experimental design used was completely randomized, with a variable number of repetitions per treatment, and the collected data were tested for normality and subsequently subjected to variance analysis by the F test, and the means compared by the Tukey test at a 5% level of probability. There was no difference in birth weight of beef cows and the birth weight of their calves as a function of the evaluated treatments. Cows in the High group had a higher average daily gain in live weight during the postnatal period than those in the Low group. This result impacted the body condition score at the end of the first reproductive period and consequently, there were higher pregnancy rates and calf production in the High treatment compared to the Low treatment. In addition, calves from cows in the High treatment also showed better postnatal development compared to calves from the Low treatment.